Associations of Short Sleep and Shift Work Status with Hypertension among Black and White Americans - Ceïde, Mirnova E. (Int J Hypertens, 2015)
Objective. The purpose of this study was to investigate whether short sleepers (<6 hrs) who worked the non-day-shift were at greater likelihood of reporting hypertension and if these associations varied by individuals' ethnicity. Methods. Analysis was based on the 2010 National Health Interview Survey (NHIS). A total of 59,199 American adults provided valid data for the present analyses (mean age = 46.2 ± 17.7 years; 51.5% were female). Respondents provided work schedule and estimated habitual sleep durations as well as self-report of chronic conditions. Results. Of the sample, 30.8% reported a diagnosis of hypertension, 79.1% reported daytime shift work, 11.0% reported rotating shift work, and 4.0% reported night shift work. Logistic regression analysis showed that shift work was significantly associated with hypertension among Blacks [OR = 1.35, CI: 1.06–1.72. P < 0.05], but not among Whites [OR = 1.01, CI: 0.85–1.20, NS]. Black shift workers sleeping less than 6 hours had significantly increased odds of reporting hypertension [OR = 1.81, CI: 1.29–2.54, P < 0.01], while their White counterparts did not [OR = 1.17, CI: 0.90–1.52, NS]. Conclusions. Findings suggest that Black Americans working the non-day-shift especially with short sleep duration have increased odds of reporting hypertension.